2019
DOI: 10.1038/s41598-019-42991-4
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA Rik-203 contributes to anesthesia neurotoxicity via microRNA-101a-3p and GSK-3β-mediated neural differentiation

Abstract: The mechanism of anesthesia neurotoxicity remains largely to be determined. The effects of long noncoding RNAs (LncRNAs) on neural differentiation and the underlying mechanisms are unknown. We thus identified LncRNA Rik-203 (C130071C03Rik) and studied its role on neural differentiation and its interactions with anesthetic sevoflurane, miRNA and GSK-3β. We found that levels of Rik-203 were higher in hippocampus than other tissues and increased during neural differentiation. Sevoflurane decreased the levels of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…In particular, we found five downregulated lincRNAs (2900076A07Rik, Gm16892, Gm4262, Gm807, and C130071C03Rik) associated to pluripotency. Specifically, 2900076A07Rik, Gm16892, Gm4262, and Gm807 activation has been correlated to reprogramming of mouse fibroblasts [37], while C130071C03Rik facilitates neuronal differentiation sponging miR-101a-3p in mouse hippocampal tissue [38].…”
Section: Role Of the Noncoding Transcriptomementioning
confidence: 99%
“…In particular, we found five downregulated lincRNAs (2900076A07Rik, Gm16892, Gm4262, Gm807, and C130071C03Rik) associated to pluripotency. Specifically, 2900076A07Rik, Gm16892, Gm4262, and Gm807 activation has been correlated to reprogramming of mouse fibroblasts [37], while C130071C03Rik facilitates neuronal differentiation sponging miR-101a-3p in mouse hippocampal tissue [38].…”
Section: Role Of the Noncoding Transcriptomementioning
confidence: 99%
“…In our previous study, we found that LncRNA Rik-203 contributes to anesthesia induced inhibition of neural differentiation (26). Rik-203 expression level was significantly lower in the hippocampus of mice exposed with 3% sevoflurane 2 h daily for 3 days (Figure 1A).…”
Section: Rik-203 Decreased By Sevoflurane and Is Critically Involved mentioning
confidence: 79%
“…Specifically, the cells were treated with 4.1% sevoflurane for 2 h daily at day 4, 5, and 6 after the start of neural differentiation to mimic the clinical several times anesthesia. The cells were harvested at day 7 during the neural differentiation, at which there're many NPCs (26). In some experiments, the cells were transfected with BDNF 12 h before the sevoflurane treatment.…”
Section: Sevoflurane Treatment Of Mice and Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of Rik-201 and Rik-203 restrained neural differentiation via acting as ceRNAs of miR-96 and miR-467a-3p, respectively, which deinhibition restricted the expression of neural differentiation-related gene Sox6 [64]. Sevoflurane was also reported to attenuating the expression of lncRNA Rik-203 that resulted in the release of miR-101-3a but lessening Glycogen Synthase Kinase-3β (GSK-3β) level, ultimately inhibited neural differentiation [65]. Furthermore, miR-128-3p is abundantly expressed in brain and emerges as a key modulator in neural differentiation, which overexpression prohibited neuron but enhanced gliocytes differentiation.…”
Section: Acting As Cerna Of Mirnamentioning
confidence: 99%